Acceptability and feasibility of HIV self-testing among transgender people in Larkana, Pakistan: Results from a pilot project. - Arshad Altaf; Muhammad Safdar Kamal Pasha; Ayesha Majeed; Wajid Ali; Ahmed Sabry Alaama; Muhammad Shahid Jamil (PLoS ONE)
Background HIV self-testing (HIVST) is an innovative HIV testing approach that effectively reaches those who do not otherwise test, including key populations (KPs). Despite potential benefits, HIVST is not currently implemented in Pakistan. The high risk of HIV among transgender (TGs) persons is among the highest risk group for HIV in Pakistan, yet knowledge of HIV status remains low in this key population group. We conducted a pilot project to assess the acceptability and feasibility of distributing HIVST to TGs in Larkana. Methods Eligible participants were 18 years or above and self-identified as transgender ("hijra"). One oral fluid HIVST kit per person was distributed free of cost in the community by trained transgender peer outreach workers (ORW). Participants could request a demonstration of the HIVST procedure before performing self-testing which was provided by the trained ORW. Demographic characteristics of participants were collected. The ORW followed up with phone calls two days later to record if HIVST kits were used, the results, and whether assistance was required. Results Between November 2020 and February 2021, 150 HIVST kits were distributed to eligible TGs. The average age of participants was 25.5 years (standard deviation: 7.0). Over a third (52, 34.7%) had no formal education, while (16, 10.6%) had attended at least five years of schooling. Over one-third (58, 38.6%) of participants were first-time testers. One hundred and thirty-nine (92.7%) participants reported their results within two days. For the remaining 11 participants, ORWs had to contact them. All participants reported using HIVST kits within three days. A majority (141, 94%) used the kit in their homes, and the remaining nine (6%) used it at the community-based organization's office. Overall, a small proportion (11, 7.3%) of participants requested a demonstration of the test procedure before performing HIVST. Four (2.7%) participants who had performed unsupervised self-tests reported reactive HIVST results; all were linked to treatment within five working days once their HIV result was confirmed. The majority (136, 90.6%) of participants felt that self-testing was easy to perform independently, and 143 (95%) reported that they would recommend HIVST to their peers. Conclusion HIVST is acceptable among TGs and identified by first-time testers as undiagnosed infections. Peer-led distribution appears to be a feasible approach for implementation in this setting. HIVST should be considered for routine implementation and scale up to reduce testing gaps among Pakistan's key population, particularly TGs.